CONCEPTUAL CONTENT OF SILENCE IN THE HERITAGE OF THINKERS AND PROVERBS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article examines the socio-linguistic and communicative aspects of silence. Based on proverbs, literary sources, and thinkers’ views, its multiple meanings are revealed. Silence is interpreted as a nonverbal unit of communication with cultural and spiritual significance.